Strategi Pengelolaan Sampah Rumah Tangga di Kecamatan Jatiasih Kota Bekasi - Sugito, Sugito; Waluyo, Subagio S; Pramitasari, Anisa (FIA Unkris Press, 2023)
This research aims to determine the strategy of domestic waste management in Jatiasih sub-District of Bekasi City, in this case whether collaborative governance theory has been applied in domestic waste management in Jatiasih sub-District of Bekasi City. This research use descriptive qualitative method, where data collection techniques are carried out by conducting interviews, documentation and obsevation. In collecting data, the researcher chose informants using purposive sampling technique where the researcher selected 6 (six) informants, namely 1 (one) Head of Technical Implementation Unit of The Environmental Service Office of Jatiasih sub-District or later called UPTD LH Jatiasih sub-District, 1 (one) person busines actor, 1 (one) trash bank activist and 3 (three) community members. The results showed that the strategy of domestic waste management in Jatiasih sub-District of Bekasi City has not applied the collaborative governance theory as a whole. In the domestic waste management, the UPTD LH Jatiasih sub-District has not optimally involved the community members in the strategy of domestic waste management in Jatiasih sub-District of Bekasi City. This relates to the fact that indicators in the collaborative governance process have not yet been fully implemented. The domestic waste management in Jatiasih sub-District of Bekasi City still faces various problems.